2019
DOI: 10.1074/jbc.ra119.007626
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent activation in EAG channels follows a ligand-receptor rather than a mechanical-lever mechanism

Abstract: Edited by Roger J. ColbranEther-a-go-go family (EAG) channels play a major role in many physiological processes in humans, including cardiac repolarization and cell proliferation. Cryo-EM structures of two of them, K V 10.1 and human ether-a-go-go-related gene (hERG or K V 11.1), have revealed an original nondomainswapped structure, suggesting that the mechanism of voltagedependent gating of these two channels is quite different from the classical mechanical-lever model. Molecular aspects of hERG voltage-gatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…Finally, it is important to note that the proposed existence of a network of interactions involving the N-terminus, the S4-S5 linker and the final portion of S6, and other C-terminal regions, is also compatible with the named ligand/receptor (allosteric) model of voltage-dependent gating (Malak et al, 2017;Malak et al, 2019), recently shown to be shared by both erg1 and eag2 channels, in which the VSD and PD are weakly coupled via a ligand constituted by the S4-S5 linker and a part of S5, and a receptor, the C-terminal part of the S6 segment (Malak et al, 2017;Malak et al, 2019). The reason why the presence of a substantial part of the S5 helix is necessary for the soluble peptides used as ligands to stabilize the closed channel state (Malak et al, 2017) remains to be established.…”
Section: New Structural and Functional Data Regarding Allosteric Inflmentioning
confidence: 76%
See 1 more Smart Citation
“…Finally, it is important to note that the proposed existence of a network of interactions involving the N-terminus, the S4-S5 linker and the final portion of S6, and other C-terminal regions, is also compatible with the named ligand/receptor (allosteric) model of voltage-dependent gating (Malak et al, 2017;Malak et al, 2019), recently shown to be shared by both erg1 and eag2 channels, in which the VSD and PD are weakly coupled via a ligand constituted by the S4-S5 linker and a part of S5, and a receptor, the C-terminal part of the S6 segment (Malak et al, 2017;Malak et al, 2019). The reason why the presence of a substantial part of the S5 helix is necessary for the soluble peptides used as ligands to stabilize the closed channel state (Malak et al, 2017) remains to be established.…”
Section: New Structural and Functional Data Regarding Allosteric Inflmentioning
confidence: 76%
“…Moreover, the possibility that the amino terminal end of the eag2 channel modulates the S4-S5 linker interaction with S6 and, as a consequence, that a hypothetical ligand/receptor gating mechanism exists, has been considered. Unfortunately, as previously shown with erg1 channels split at the S4-S5 linker, deletions of amino terminal sequences of eag2 obliterated by themselves the functional expression of the channels, complicating the possible interpretation of the data (Malak et al, 2019). In any case, it is tempting to speculate that the existence of allosteric components for modulation of gating, documented in Kv10-12 (EAG) channels, but also in other Kv relatives (Barros et al, 2019), constitutes a way to provide evolutionary functional diversification to a common and particularly successful 6TM1P molecular channel design.…”
Section: New Structural and Functional Data Regarding Allosteric Inflmentioning
confidence: 98%
“…In this work, we used a S4-S5 L mimicking peptide approach to test whether voltage-gated sodium channels follow the ligand/receptor model previously proposed for hK V 7.1 25 , hK V 11.1 26 and hK V 10.2 29 channels. We identified one activating S4-S5 L peptide in Na V Sp1 and four in hNa V 1.4, suggesting that Na V channels follow a ligand/ receptor model of voltage-dependent gating (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the observation that specific S4-S5 L -mimicking peptides inhibit hK V 7.1 and hK V 11.1 channels, by replacing the endogenous segment in the binding pocket 25,26 . This mechanism was recently extended to hK V 10.2 channels 29 .…”
mentioning
confidence: 97%
See 1 more Smart Citation